Seal performance analysis and lifetime evaluation of capsule plugging glue. (January 2022) - Wang, Li-Na; Sun, Wei; Sun, Li-Chen; Yan, Rong-Xin; Wang, Qian; Wang, Hao; Su, Liang; Meng, Dong-Hui; Qi, Guang-Ming; Guo, Qi; Zhou, Qiang; Wang, Meng-Chen; et al.
Abstract: The capsule plugging glue as a repair tool is used to block the leak of the space station in orbit. Therefore the stringent requirements of its seal performance and life are put forward to ensure that the space station has excellent seal performance in orbit. It protects the life of cosmonaut, and maintains the lifetime of the space station. But the seal performance analysis and lifetime evaluation of capsule plugging glue has not carried out at present. Based on this, the mechanics performance parameters of the capsule plugging glue before and after the aging test are obtained by the correlative experiment. And then the thermal oxygen aging models of the capsule plugging glue are established in the storage and service status based on the time-temperature equivalence theory respectively, and realized to predict the lifetime of the capsule plugging glue in the two working status. In addition, the leakage performance of the capsule plugging glue, which is used to block the leak, is measured by the spray probe method. And then the change law of the seal performance of capsule plugging glue with the increase of aging time is obtained in the storage and service status. Highlights: The capsule plugging glue as a repair tool is used to block the leak of the space station in orbit. Therefore the stringent requirements of its seal performance and life are put forward to ensure that the space station has excellent seal performance in orbit. It protects the life of cosmonaut, and maintains the lifetime of the space station. But the seal performance analysis and lifetime evaluation of capsule plugging glue has not carried out at present. Based on this, the mechanics performance parameters of the capsule plugging glue before and after the aging test are obtained by the correlative experiment. And then the thermal oxygen aging models of the capsule plugging glue are established in the storage and service status based on the time-temperature equivalence theory respectively, and realized to predict the lifetime of the capsule plugging glue in the two working status. In addition, the leakage performance of the capsule plugging glue, which is used to block the leak, is measured by the spray probe method. And then the change law of the seal performance of capsule plugging glue with the increase of aging time is obtained in the storage and service status.